Influence of Essential Roles of Leadership in Implementing Change - Siti Hazrah; Nuri Aslami (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Organizational changes can be technical, structural, personal, and physical changes that require new knowledge, skills, and culture. When making changes to an organization, there are many factors that prevent it, such as an organizational culture that resists the changes and weak leadership. Leadership is the driving force behind the success of an organization. Therefore, change leaders need to set change goals, make decisions about them, and decide what changes to make. Using literature review methods, this study aims to determine the implications of the important role of leadership in making change...